Dasar Kemampuan Mengajar: Analisis Deskriptif Pada Mahasiswa PGSD Sebagai Bahan Tindak Lanjut Perkuliahan - Arina Wulandari; Wulida Makhtuna; Mashud (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This study aims to analyze the basic teaching skills of the students of the Elementary School Teacher Education study program as follow-up material for Civics learning course. This type of research is quantitative research using survey methods. The research subjects were the students of the Elementary School Education Study Program who programmed the Civics Learning course, totaling 36 students. The research instruments used are the teacher supervision assessments which are divided into preliminary activities, core activities, and closing activities, which includes the elements of the basic teaching skills namely; 1) opening the lesson, 2) material mastery 3) teaching and learning interactions, 4) language use, 5) classroom management, 6) learning evaluation, and 7) closing the lesson. Data collection procedures include students lesson preparation documents, online micro teaching practice, lecturers’ observation, and the learning assessments carried out by the students. The data analysis uses descriptive quantitative technique applying percentage analysis. The research results are divided into four categories namely; (1) very good category is in the language use skill component, (2) good category is in the opening skill component, the interaction of the learning process, and the learning closing skill, (3) the moderate category is in the class management and (4) the lack category is in the components of material mastery and learning evaluation skill.